Comparison of the Effects of Isoflurane and Sevoflurane General Anaesthesia after Induction by Propofol on Clinical and Physiological Measurements in Calves - Yakan, Selvinaz; Aksoy, Ozgur (Acta Scientiae Veterinariae, 2019)
Background: In veterinary surgical operations for cats and dogs, inhalation anaesthesia is known to be a good option for general anaesthesia in long operations or emergency cases. Studies have revealed that during inhalation anaesthesia, the heart and respiratory functions of the animals are more stable compared to injectable anaesthesia. However, there are few studies performed with the use of inhalation anaesthesia in ruminants. In this research, the goal is to evaluate the effects of isoflurane and sevoflurane after induction with propofol in calves based on clinical and physiological parameters and to find a more reliable strategy for general anaesthesia in ruminants. Materials, Methods & Results: The research was carried out on 30 calves, from new-born up to 3-months-old, undergoing surgery operation. Each group consisted of 15 animals that were divided as isoflurane and sevoflurane. For premedication, atropine was administered at a dose of 0.04 mg/kgvia subcutaneous injection in calves. For induction, 15 min after atropine application, propofol was given at 5-6 mg/kgvia intravenous infusion. Then, endotracheal intubation was performed and inhalation anaesthesia began at 5 min after induction. In the isoflurane group, the onset of anaesthesia concentration was set to 3-5% and the maintenance was set to a concentration of 1.5-3%. In the sevoflurane group, the onset of anaesthesia concentration was set to 5-7% and the maintenance was set to a concentration of 2.5-4%. To monitor the calves, the heart rate (HR), the pulse rate (PR), the systolic blood pressure (SBP), diastolic blood pressure (DBP), the respiratory rate (RR), the rectal temperature (RT) and the electrocardiogram (ECG) measurements were recorded before anaesthesia, the premedication, the induction periods, at 5, 15, 30, 45, 60, and 75 min after the onset of inhalation anaesthesia during the operation period. Blood samples were taken before anaesthesia, premedication, induction periods, at 30 and 75 min during the operation and the red blood cell (RBC) count, white blood cell (WBC) count, the amount of haemoglobin (HGB), the haematocrit concentration (HCT), and the platelet (PLT) count were evaluated. Based on the findings, isoflurane and sevoflurane suppressed the cardiovascular system minimally. Both anaesthetic agents caused decreases that did not exceed the physiological limits compared to the measurements taken before the initiation of anaesthesia. Although no significant differences were detected between the groups (P > 0.05) at clinical parameters, the RT differences were regarded as statistically significant according to the measurements that were taken before anaesthesia at all measurement times (P < 0.05). In both groups, the changes that occurred in the P wave, the PR interval, and in the QRS, R and T waves remained within the reference values given in the literature. Both anaesthetic agents have similar effects on the ECG. The dramatic no changes throughout anaesthesia in terms of the amount of HGB and HCT, the RBC, the WBC, and the PLT were not statistically significant, which may be associated with good tissue perfusion. Discussion: Since no serious complications occurred with either anaesthetic option, we have concluded that isoflurane and sevoflurane have similar effects on the cardiopulmonary systems of calves. In addition, the effects of propofol, which is used for induction, have been evaluated and observed and this drug is an effective and reliable option to initiate inhalation anaesthesia. The research on the use of this anaesthetic in calves is limited and most of the existing studies investigated its combination with injectable anaesthetics. As a result, in this research, we concluded that isoflurane and sevoflurane induce similar physiological measurement results, blood parameters, and ECG results and that both anaesthetics cause minimal complications.